Stability of DNA-tethered lipid membranes with mobile tethers - Chung, Minsub (Langmuir : the ACS journal of surfaces and colloids, 2011)
We recently introduced two approaches for tethering planar lipid bilayers as membrane patches to either a supported lipid bilayer or DNA-functionalized surface using DNA hybridization (Chung, M.; Lowe, R. D.; Chan, Y-H. M.; Ganesan, P. V.; Boxer, S. G. J. Struct. Biol.2009, 168, 190-9). When mobile DNA tethers are used, the tethered bilayer patches become unstable, while they are stable if the tethers are fixed on the surface. Because the mobile tethers between a patch and a supported lipid bilayer offer a particularly interesting architecture for studying the dynamics of membrane-membrane interactions, we have investigated the sources of instability, focusing on membrane composition. The most stable patches were made with a mixture of saturated lipids and cholesterol, suggesting an important role for membrane stiffness. Other factors such as the effect of tether length, lateral mobility, and patch membrane edge were also investigated. On the basis of these results, a model for the mechanism of patch destruction is developed